IPTEKS PELAYANAN PRIMA TERHADAP KINERJA BAGIAN KEUANGAN ATAS KLAIM DANA PENSIUN PT TASPEN (PERSERO) CABANG MANADO - Midu, Mutia Larasati S.; Pinatik, Sherly (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT TASPEN (Persero) Manado Branch is a State-owned business entity whose task is to manage social insurance programs which in this case handle the pension fund and old age savings program. Then, in its service, PT TASPEN (Persero) certainly requires the existence of procedures that are implemented in order to achieve customer satisfaction. Good service in insurance companies is certainly very influential on the assessment of financial performance and the existence of companies in shutter outside the company. Influence on financial performance because in the implementation of its main duties the part that regulates the problem of claiming funds is the field of services and benefits, where the fields are directly related to customers. So it is very important that there is good customer service so that it can carry out its duties and responsibilities in accordance with the objectives of the company, which is to become a trusted, clean and healthy pension and THT social insurance provider.Keywords : Insurance, pension fund, Costumer Service